(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2022)
The singular is the foundation of the first and second simple intelligibles, as well as of predication and syllogisms. The question is whether there is a possibility of obtaining the concept of singular that substantiates the correspondence of the mental domain with the concrete order. In fact, man knows intellectually and sensitively, modi sciendim whose direct object, respectively, the universal and the singular, since he cannot, as will be seen, know, judge and reason without conversio ad phantasmata. It will be seen that the soul can know its own nature, knowing that it knows by conversio ad phantasmata, and also make a reflection on the whole human process. At this point, it will be seen whether the intelect can indirectly and directly aim at the intention of individuality to acquire the concept of singular.